The manifestations of social marginalization in Tunisia and the problem of protection and inadequate care following the political changes after the events of 2011 - Alhafdaoui, Saad (Social Sciences Journal, 2020)
The issue of groups with special needs and social marginalization is still one of the major national issues that have become politically confusing, socially fragmented, emotionally frustrating and economically embarrassing... Interventions in this area continue to be poorly supported, accompanied and followed up and do not meet the specific needs of these groups Which was referred to in some of the literature as “hard core". The high proportions of this phenomenon at the quantitative, qualitative and regional level were revealed to the public opinion after the Tunisian revolution, which revealed social groups suffering from misery and privation, lacking the most basic necessities of life. The plans for economic and social development have long been devised only on a number of occasions for political purposes, and therefore the development policies in this area have been temporary painkillers or a Seizia work that defines strong breakthroughs and vague ends.